Efektivitas Lembar Kerja Siswa Melalui Metode Reading Guide Untuk Meningkatkan Pemahaman Membaca Literal dan Inferensial Siswa Kelas V SDN 1 Jabranti - Afrillia Maharanie; Oman Suryaman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to determine the effectiveness of using Student Worksheets (LKS) through the reading guide method on the literal and inferential reading comprehension skills of fifth-grade elementary school students. This study employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The sample consisted of 25 students, including 14 students in the experimental class and 11 students in the control class. Data were collected through tests in the form of pretest and posttest, observation, and documentation. The data were analyzed using normality tests, homogeneity tests, paired sample t-test, and independent sample t-test with the assistance of SPSS version 26. The results showed that the average reading comprehension score in the experimental class increased from 64.286 in the pretest to 89.050 in the posttest. The paired sample t-test results showed a significance value of 0.000 < 0.05, indicating a significant difference between students’ reading comprehension skills before and after learning using LKS through the reading guide method. The independent sample t-test also showed a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control classes. Therefore, the use of LKS through the reading guide method was effective in improving the literal and inferential reading comprehension skills of fifth-grade elementary school students.